(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
These “notes” are a doctrinal dissertation on the legal system established by the Federal Constitution of the Argentine Republic. The constitutional foundation of the Argentine State is addressed, as well as topics relating to constitutional creation, realization, change and interpretation. In this sense, it is emphasized that the Federal Constitution contains the reasons for Argentine law. For this reason, only the Fundamental Writ confers with supreme authority all the institutional regulation that constitutes the relations of citizenship and the controlled exercise of powers, even providing its own protocol to validate any reform of its enunciations, always respecting the intangibility of the republic as a form of government and democracy as a form of political orientation of the state. In this respect, it is clear that democracy shapes harmonious coexistence in society, and a citizenry in harmony guarantees lasting community peace, the highest mission of the Fundamental Writ of the Argentine State. In this way, it is shown that, in the 21st century, the community coexistence of citizens and their peaceful growth must develop in a world of rules, the one supremely ordered by the Fundamental Scripture, the only authority to make the ideal of the rule of law attainable. Therefore, it is emphasized that, even in the face of different community needs, nothing justifies the creation of Law above the Constitution, since there is no source of supreme need that can be elevated or equated to the Fundamental Law, with the understanding that in a constitutional state nothing or no one should have a higher hierarchy than the Highest Law.